PENGANGKATAN PENYANDANG DISABILITAS SEBAGAI APARATUR SIPIL NEGARA BERDASARKAN PERATURAN PERUNDANG-UNDANGAN: Appointment of Persons With Disabilities as State Civil Apparatus Based On Laws and Regulations - Adrian Cahdani Cakti; Yogo Pamungkas (AMICUS CURIAE, 2024)
Along the way, the Recruitment of State Civil Apparatus for Persons with Disabilities is still not in accordance with existing regulations. Therefore, it is necessary to optimize the recruitment process for people with disabilities to be in accordance with the regulations governing it. The issue raised is whether the recruitment selection for Persons with Disabilities as State Civil Apparatus in 2019 is in accordance with the Laws and Regulations in the field of civil servants? And is the availability of positions or jobs for Persons with Disabilities as State Civil Apparatus in 2019 in accordance with the Laws and Regulations in the field of civil servants? The type of research is Normative with the nature of descriptive research analysis and uses secondary data. Then writing is analyzed qualitatively by drawing deductive logic conclusions. Thus, the result of the first analysis is that the series of recruitment processes for the State Civil Apparatus for Persons with Disabilities is still not in accordance with Article 53 paragraph (1) of Law Number 8 of 2016 and Permen-PANRB Number 23 of 2019 that the minimum allocation for persons with disabilities is 2% of the total allocation in each government agency, both central and regional. The second analysis is that regulations regarding the availability of formations and positions that can be filled and cannot be filled for civil servants with disabilities become an obstacle to the presence of persons with disabilities in Government Agencies due to inconsistencies between written regulations and their implementation.